Analisis Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Pemerintah Kota Bogor Tahun 2024 - Mila Yuniar; Risma Aulia; Shafira Samrotul Fuadah; Fadjar Tri Sakti (Jurnal Widya Mahavira, 2026)
Regional financial management is a crucial aspect in supporting governance and regional development, particularly in the era of regional autonomy that demands fiscal independence and public accountability. Regional financial conditions reflect the ability of local governments to manage revenue and expenditure sources effectively and efficiently. Bogor City, as one of the strategic cities in West Java Province, has interesting fiscal dynamics to study. This study uses a qualitative descriptive approach utilizing secondary data in the form of Regional Revenue and Expenditure Budget (APBD) documents and the Regional Government Financial Report (LKPD) of Bogor City for Fiscal Year 2024. The analysis results show that the regional financial condition of Bogor City is relatively stable and has improved compared to the previous year, as indicated by an increase in regional revenue, a decrease in the budget deficit, and an increase in the Budget Financing Surplus (SILPA). However, the regional revenue structure is still dominated by transfer revenue, so the level of fiscal independence is in the low to moderate category, although the effectiveness of Regional Original Revenue collection shows very good performance.